2011
DOI: 10.1002/ange.201008051
|View full text |Cite
|
Sign up to set email alerts
|

Is Water Necessary for Contact Electrification?

Abstract: Hatte Thales Recht? Entgegen früheren Berichten kann es ohne Wasser zu einer Kontaktelektrifizierung kommen. Zugleich hilft Wasser, die entwickelten Ladungen zu stabilisieren. Wasserfreie Bedingungen wurden gewährleistet, indem alle Schritte unter Öl durchgeführt wurden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Naively, one might have expected that the glass would have uniform potential following contact, because (unlike many polymers) it is hydrophilic and likely to have adsorbed water that would allow ions to migrate. Adsorbed water from humidity plays a role in the magnitude of the contact charge density and the resistivity [31,32], but apparently it does not lead to charge uniformity. By contrast, the gold electrodes in our experiment showed little charge heterogeneity, which may be a result of the high density of conduction electrons in the bulk.…”
Section: Discussionmentioning
confidence: 99%
“…Naively, one might have expected that the glass would have uniform potential following contact, because (unlike many polymers) it is hydrophilic and likely to have adsorbed water that would allow ions to migrate. Adsorbed water from humidity plays a role in the magnitude of the contact charge density and the resistivity [31,32], but apparently it does not lead to charge uniformity. By contrast, the gold electrodes in our experiment showed little charge heterogeneity, which may be a result of the high density of conduction electrons in the bulk.…”
Section: Discussionmentioning
confidence: 99%
“…Charging parameters which influence the type of contact, contact stress, number of contacts, value of exchange charge: Feeding rate (throughput) [24] Material of the charger walls and its electric properties [51,58,72] Type of charger unit and its parameters (e.g. travel speed of the belt, vibration frequency of the plate charger) [29] Time between charging and separation [49,57] Separation parameters which influence the forces in the system: Type of electrode (rotating, plate [24] Magnitude of electric field and distance between the electrodes [52] Isolation/modification of electrodes [32] Actions before separation which influence the charging behavior: Storing, milling, transporting (precharging, contamination, aging) [78] Conditioning chamber (heating, drying, introduction of chemicals on the mineral surfaces) [104] Parameters which change charging behavior of particles: Humidity [29,47] Atmosphere [114] Temperature [47,48,58] Light…”
Section: Insulators Characteristics Powder Characteristics Equipment mentioning
confidence: 99%
“…Long-term decay of charged insulators: A comparison of the temporal decay of contact charge on a polymer surface in humid air (relative humidity 40 % r.H.) and in water-free environment (in paraffin oil) [114] showed that the decay kinetics is of first-order, and that the corresponding charge decay rates vary with environmental conditions (10 -3 s -1 and 10 -2 s -1 in air and oil, respectively). This suggests that the charge decay is associated with a different stability of the introduced charges under humid air and paraffin oil.…”
Section: Discharging Decay and Evolution Of The Introduced Chargementioning
confidence: 99%
“…However, recent theories suggest that for some insulators, the charge carriers are ions, which exist on polymer surface due to preferential adsorption of hydroxide ions from atmosphere (McCarty and Whitesides, 2008). Thus, tribocharging can be considered as a combination of these aforementioned processes and particularly for non-electrolytes, electrons can be considered as the main charge transfer carriers (Karner and Urbanetz, 2011;Baytekin et al, 2011). Considering these factors, this paper focuses on electron exchange mechanism for tribocharging of insulators and hence estimates the work function of all surfaces.…”
Section: Introductionmentioning
confidence: 97%